Evaluating the impact of Matrilin-1 gene polymorphisms on mandibular prognathism: A meta-analysis - Pooja Kurmi; Prasad Nalabothu; Shubhasmita Sahoo; Henu Kumar Verma; Srinivas Gosla Reddy; L.V.K.S. Bhaskar (Journal of Oral Biology and Craniofacial Research)
Introduction: Matrilin-1 was shown to regulate the formation of cartilage matrix and to promote chondrocyte differentiation. This meta-analysis aims to synthesize evidence regarding the link between mandibular prognathism (MP) risk and the polymorphisms in the MATN1 gene. Materials and methods: Relevant publications were retrieved by searching the PubMed, Web of Science, and Google Scholar databases. The association between MP and the MATN1 gene polymorphisms (rs20566, rs1065755) was assessed by calculating odds ratios (ORs) and 95 % CIs. Between studies, heterogeneity was identified using the Cochrane Q test and I2 statistics. To assess the robustness of the meta-analysis sensitivity analysis was performed. The web tool MetaGenyo was used to conduct a meta-analysis. Results: A total of four Asian and one Caucasian study were eventually taken for meta-analysis. Overall, the MATN1 rs20566 and rs1065755 polymorphisms are not associated with elevated risk of MP (rs20566 AA + AG versus GG OR = 1.35, 95 % CI = 0.32–5.67; rs1065755 TT + CT versus CC OR = 2.02, 95 % CI = 0.87–4.68). The degree of heterogeneity is found to be large for the MATN1 polymorphisms (for rs20566, I2=89 %, and for rs1065755, I2=60 %). Conclusions: In conclusion, this meta-analysis did not provide evidence for the link between MATN1 polymorphisms and MP. However, the results conflict with the biological plausibility that matrilin-1 levels modulate cartilage development. Therefore, careful interpretation is needed, and further research is recommended.